2019
DOI: 10.1177/0192512119881710
|View full text |Cite
|
Sign up to set email alerts
|

Crook!: The impact of perceived corruption on non-electoral forms of political behaviour

Abstract: Anti-corruption claims have been at the core of many mass mobilizations worldwide. However, the nexus between corruption and collective action is often overlooked. Bridging social movement and corruption studies, this article contends that believing in extensive corruption has a positive impact on non-electoral forms of participation. But this effect is uneven across the population and contingent upon the individual’s political interest and education. Using survey data from 34 countries, the analysis confirms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
1
11
0
1
Order By: Relevance
“…Furthermore, these gender differences are more pronounced in countries with low corruption whereas the effect is marginal in societies where corruption is widespread, which is contrary to the expectation in Hypothesis 2. These findings are in line with those reported by Bazurli and Portos (2019), who also find that perceptions of endemic corruption are likely to engage citizens to take part in extra-institutional behavior such as boycotts and public protests.…”
Section: Discussion Of the Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, these gender differences are more pronounced in countries with low corruption whereas the effect is marginal in societies where corruption is widespread, which is contrary to the expectation in Hypothesis 2. These findings are in line with those reported by Bazurli and Portos (2019), who also find that perceptions of endemic corruption are likely to engage citizens to take part in extra-institutional behavior such as boycotts and public protests.…”
Section: Discussion Of the Resultssupporting
confidence: 91%
“…We here examine a potential piece in this puzzle by examining how the links between corruption perceptions and political participation differ for men and women. Previous studies show that the effect of perceptions of corruption differ across social groups (Agerberg 2019;Bazurli and Portos 2019), but the differences between men and women remain unclear. It has been a cause for concern that previous research has found a consistent gender gap in political participation (Dalton 2017;Verba, Schlozman, and Brady 1995).…”
Section: 行分析。我们的结果显示,当面对腐败时,女性变得更有可能参与 投票,而男性则在面对腐败时更有可能进行以挑战精英为形式的参 mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this research combines different forms of political participation, including taking part in a demonstration, signing a petition, participating in a boycott, attending a political meeting or rally, contacting a politician, contacting the media, and donating money or raising funds for a political cause in the past year, into one dependent variable. Corruption, according to this research, has a positive impact on non-electoral forms of political participation, but the effect is primarily among people with lower levels of education and less political interest who hold anti-elitist views and tend to engage in noninstitutionalized forms of political participation (Bazurli and Portos 2019).…”
Section: Influence Of Corruption On Institutionalized and Non-institumentioning
confidence: 73%
“…Although participation in elections is one of the most critical aspects of political participation in developing countries, in recent years non-electoral participation, especially protest methods, has also been expanding to influence governments. In this regard, it seems that one of the vital factors contributing to the development of new ways of political participation in these countries is the citizens' corruption perceptions (Bazurli and Portos, 2019;Kostadinova and Kmetty, 2019;Beyerle, 2014;Landell-Mills, 2013). In other words, as Van de Walle and argue, many citizens participate in protest activities in reaction to perceptions of corruption in society.…”
Section: Introductionmentioning
confidence: 99%